Wawqi: de alter ego a hermano - Fossa Falco, Lydia (2025)
Wayki is a word that has become fashionable recently, but it is an old word. Texts from the 16th century and the beginning of the 17th exhibit examples of its precursor wawqi that will help us investigate its function in Inka world: chronicles and reports written by Spanish laypeople who described early Tawantinsuyu, and Vocabularies and Lexicons compiled by priests. The semantic and semiotic analyses carried out will serve to clarify the pre-Hispanic senses and meanings of wawqi in context and bring us closer to its true role in ancient Andean culture. I will also show how the colonization of the Quechua language by Spanish has occurred, especially during the 16th century, and the active participation the clergy had in this operation of transformation of one of the most important indigenous Andean languages.